2021
DOI: 10.1002/14651858.cd013620.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Alternating pressure (active) air surfaces for preventing pressure ulcers

Abstract: Background Pressure ulcers (also known as pressure injuries, pressure sores, decubitus ulcers and bed sores) are localised injuries to the skin or underlying soft tissue, or both, caused by unrelieved pressure, shear or friction. Alternating pressure (active) air surfaces are widely used with the aim of preventing pressure ulcers. Objectives To assess the effects of alternating pressure (active) air surfaces (beds, mattresses or overlays) compared with any support surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 160 publications
0
26
0
8
Order By: Relevance
“…The use of pressure relief devices, such as specialist mattresses, is one of the key PU prevention practices in PU prevention guidelines 3 even though the evidence is somewhat uncertain about the differences in the effects of these devices. 34 In addition, not all the devices, such as water‐filled gloves or sheepskins, are recommended as they might cause more harm than good. 1 Documentation as a PU prevention practice was used quite regularly among the participating nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The use of pressure relief devices, such as specialist mattresses, is one of the key PU prevention practices in PU prevention guidelines 3 even though the evidence is somewhat uncertain about the differences in the effects of these devices. 34 In addition, not all the devices, such as water‐filled gloves or sheepskins, are recommended as they might cause more harm than good. 1 Documentation as a PU prevention practice was used quite regularly among the participating nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fibres on the surfaces of electric blankets are longer, which also increases friction and thereby generates heat, increasing the risk of PIs as well. 38,39 In this study, in the use of thermoregulation devices, the regression coefficient of the use of electric blankets was significantly positive. The results of this study also confirmed that using electric blankets during surgery increases the risk of PIs and that said risk is 8.14 times higher than the risk of PIs in patients not using electric blankets.…”
Section: Discussionmentioning
confidence: 50%
“…Pressure redistributing or off-loading measures in health care are supported by limited evidence; nevertheless, their use is recommended in clinical practice guidelines for pressure injury prevention 8,21. Strategies include regular turning and repositioning, use of pressure redistributing devices, and off-loading pressures on the heel 8,21–23. Many patients within our study had some form of pressure injury redistribution such as regular turning and repositioning and use of pressure redistributing support surface (mattress).…”
Section: Discussionmentioning
confidence: 90%